Intragranular twinning, detwinning, and twinning-like lattice reorientation in magnesium alloys. (December 2016) - Wu, Wei; Gao, Yanfei; Li, Nan; Parish, Chad M.; Liu, Wenjun; Liaw, Peter K.; An, Ke
Abstract: Deformation twinning plays a critical role on improving metals or alloys ductility, especially for hexagonal close-packed materials with low symmetry crystal structure. A rolled Mg alloy was selected as a model system to investigate the extension twinning behaviors and characteristics of parent-twin interactions by nondestructive in situ 3D synchrotron X-ray microbeam diffraction. Besides twinning-detwinning process, the "twinning-like" lattice reorientation process was captured within an individual grain inside a bulk material during the strain reversal. The distributions of parent, twin, and reorientated grains and sub-micron level strain variation across the twin boundary are revealed. A theoretical calculation of the lattice strain confirms that the internal strain distribution in parent and twinned grains correlates with the experimental setup, grain orientation of parent, twin, and surrounding grains, as well as the strain path changes. The study suggests a novel deformation mechanism within the hexagonal close-packed structure that cannot be determined from surface-based characterization methods. Graphical abstract: